Channel Estimation on 60GHz Wireless System Based on Subspace Pursuit - Baokai Zu; Xinyuan Xia; Kewen Xia; Chuanjian Bai (Institute of Advanced Engineering and Science, 2014)
Due to the channel with characteristic of sparse multi-path in the 60 GHZ wireless communication system, the channel estimation problem can be attributed to that of sparse signals recovery. And with the consideration of the subspace pursuit (SP) algorithm is superior to the orthogonal matching pursuit (OMP) at reconstruction precision, the channel estimation technique based on the SP algorithm is presented in the 60 GHZ wireless communication system, First, design the OFDM multi-carrier modulation communication system. Then, establish the channel estimation mathematical model with indoor Line-of-sight. Finally, complete the reconstruction of sparse signals using SP algorithm. The experimental results and comparison analysis show that the presented technique based on the SP algorithm provides better channel estimation performances in the same pilot conditions, and it is superior to the technique based on OMP algorithm and the technique based on least square (LS) algorithm.